Banjar Customary Law as a Living Law: An Ehrlichian Analysis of Consensus-Based Dispute Resolution and Social Restoration - Rahmiati, Rahmiati; Muslim, Abdul Aziz; Perdana, Gusti Muhammad Raja Putra; Khairunnisa, Khairunnisa (Anterior Jurnal, 2026)
This article examines the status of Banjar customary law as a living law and its potential integration into regional regulations in South Kalimantan using Eugen Ehrlich’s theory of the living law. This normative legal study employs a conceptual approach, a statutory approach, and document analysis of both national and regional regulations. The findings demonstrate that Banjar customary law fulfills the characteristics of a living law, possessing strong social legitimacy and functioning as a mechanism for dispute resolution grounded in deliberation and social restoration. Nonetheless, its integration into the formal legal system faces challenges, including the absence of a regional recognition regulation (Perda Rekognisi), the lack of limited codification, and normative disharmony between customary law and state law. This study proposes an integration model based on recognition-oriented regional regulations, limited codification, and synergy with the national restorative justice framework. The findings contribute conceptually to strengthening legal pluralism in Indonesia and formulating regionally responsive policies rooted in local values.